1991
DOI: 10.1093/brain/114.4.1903
|View full text |Cite
|
Sign up to set email alerts
|

The Hyperekplexias and Their Relationship to the Normal Startle Reflex

Abstract: The startle response to unexpected auditory and somaesthetic stimulation was studied in 8 patients with hereditary or symptomatic hyperekplexia. It was abnormal in its resistance to habituation and in its exaggerated motor response. Both noise and taps to the face and head elicited a normal early blink response, separate from the subsequent true startle reflex. The earliest reflex EMG activity recorded after the blink was in sternocleidomastoid. EMG activity in masseter, and trunk and limb muscles followed lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
165
4
3

Year Published

1994
1994
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 219 publications
(181 citation statements)
references
References 0 publications
9
165
4
3
Order By: Relevance
“…Hyperekplexia is defined as an exaggerated motor response to auditory, somesthetic, or visual stimuli that is resistant to habituation and may be characterized by either a brief pathologic startle reflex or a sustained tonic spasm. 12 An appropriate stimulus produces a …”
Section: Discussionmentioning
confidence: 99%
“…Hyperekplexia is defined as an exaggerated motor response to auditory, somesthetic, or visual stimuli that is resistant to habituation and may be characterized by either a brief pathologic startle reflex or a sustained tonic spasm. 12 An appropriate stimulus produces a …”
Section: Discussionmentioning
confidence: 99%
“…The paucity of responses of the biceps and thenar muscles made the comparison less reliable. The onset latencies of the orbicular muscle of the eye were not prolonged in the minor HE com pared with those in the control group, but their analysis is com plicated because they comprise 2 types of reflexes: the startle reflex and the blink reflex.15 Pro longed onset latencies in a patient with the hereditary minor HE were also described by Brown et a l 10 Mean onset latencies increased in the 4 muscles in the follow ing order: the orbicular muscle of the eye, the sterno cleidomastoid muscle, the biceps muscle, and the the nar muscle in the 2 patient groups in our study, which may be caused by the innervation of the muscles from the startle generator.10 In the control group, the onset latency of the thenar muscle was shorter than that of the biceps muscle, but this may be caused by the small number of thenar responses. The onset latencies in the minor HE group were too long to be compatible with a startle response; the same refers to the differences in latencies between the sternocleidomastoid and the biceps muscles (51.8 milliseconds) and between the biceps and thenar muscles (53.2 milliseconds),10, 15 Thompson et al16 investigated voluntary stimulussensitive jerks in patients and controls and found that it was possible to distinguish voluntary jerks from the ste reotyped electrophysiological characteristics of the startle response of brain-stem origin.…”
Section: Commentmentioning
confidence: 66%
“…Electromyography showing exaggerated, synchronized rhythmic myoclonic contraction of all extremities, which was easily elicited by sensory stimulation, was more compatible with BRRM (Brown et al 1991;Rothwell 1996;Hallett 2002) than with other types of myoclonus, including that of cortical or spinal origin, although additional electrophysiological data were not available. The possibility of hyperekplexia was ruled out by examining GLRA1 gene mutation.…”
Section: Discussionmentioning
confidence: 87%
“…The acute type has not been studied intensively but probably originates in the brainstem (Hallett 2000). One such condition is brainstem reticular reflex myoclonus (BRRM), characterized by sudden generalized shock-like movements that can be elicited by sensory stimulation (Brown et al 1991;Rothwell 1996). Most patients who develop post-hypoxic myoclonus are between the ages of 15 and 60 years (Frucht 2002), whereas such movement disorders are very rarely reported in childhood.…”
mentioning
confidence: 99%